Environmental Quality Index Analysis in the Ancient Buyan-Beratan-Batur - I Gede Budiarta (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the Water Quality Index in the Buyan-Beratan Ancient Caldera area; analyze the Land Quality Index in the Buyan-Beratan Ancient Caldera area; and map the distribution of the Environmental Quality Index in the Buyan-Beratan Ancient Caldera area. The method used includes a spatial approach with water quality data processing based on the Calculation of Water Quality Status using the Pollutant Index method with reference to class II water quality standards according to Attachment VI of Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management; Land quality was analyzed using a geological and geomorphological approach. The results of the study show that the distribution of water quality both horizontally and vertically in the study area is classified as moderate (class 2), because several parameters are above drinking water quality standards, including: turbidity, pH, NH3, F, Fe, DO, BOD, COD and Coliform Bacteria. Land quality in the study area is suitable for cultivating seasonal crops, such as vegetables and fruits.